2015
DOI: 10.2106/jbjs.n.01215
|View full text |Cite
|
Sign up to set email alerts
|

Management of End-Stage Ankle Arthritis: Cost-Utility Analysis Using Direct and Indirect Costs

Abstract: Economic and decision analysis Level II. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 38 publications
0
41
0
Order By: Relevance
“…As with surgical reconstruction, there are few studies that have compared conservative management for ankle OA with surgical fusion or replacement for the ankle. Nwachukwu et al 72 performed a cost-effectiveness analysis of operative and non-operative treatments with an emphasis on incremental cost-effectiveness ratio, which considers direct and indirect costs along with QOL years. Their analysis was based on the cost of ankle fusion ($16 754) and ankle replacement ($21 423) from the 2012 Nationwide Inpatient Sample from the USA.…”
Section: Section A: Establishing Las Prevalence and Burdenmentioning
confidence: 99%
See 1 more Smart Citation
“…As with surgical reconstruction, there are few studies that have compared conservative management for ankle OA with surgical fusion or replacement for the ankle. Nwachukwu et al 72 performed a cost-effectiveness analysis of operative and non-operative treatments with an emphasis on incremental cost-effectiveness ratio, which considers direct and indirect costs along with QOL years. Their analysis was based on the cost of ankle fusion ($16 754) and ankle replacement ($21 423) from the 2012 Nationwide Inpatient Sample from the USA.…”
Section: Section A: Establishing Las Prevalence and Burdenmentioning
confidence: 99%
“…Their analysis was based on the cost of ankle fusion ($16 754) and ankle replacement ($21 423) from the 2012 Nationwide Inpatient Sample from the USA. Ankle replacement procedures are more expensive than non-operative management, but this technique was optimal in 83% of the analyses when considering direct and indirect costs, along with factors that impact QOL 72. This means that the best option for patients with end-stage OA is a very costly surgery.…”
Section: Section A: Establishing Las Prevalence and Burdenmentioning
confidence: 99%
“…The authors concluded that total ankle arthroplasty was the most cost-effective strategy, with an incremental cost of $14,500 per QALY compared to nonoperative management. Furthermore, total ankle arthroplasty resulted in a $5900 lifetime savings over nonoperative management and an $800 lifetime savings over ankle fusion [30]. This study elegantly illustrates the point that orthopedic technology with high initial cost may eventually provide greater cost-effectiveness and value in the long term.…”
Section: Total Joint Replacementmentioning
confidence: 68%
“…The cost-effectiveness of total ankle arthroplasty has also been evaluated, comparing it with ankle fusion or nonoperative management for the treatment of end-stage ankle arthritis [30]. The authors concluded that total ankle arthroplasty was the most cost-effective strategy, with an incremental cost of $14,500 per QALY compared to nonoperative management.…”
Section: Total Joint Replacementmentioning
confidence: 99%
“…Analysis of the direct and indirect costs associated with either intervention, concluded that total ankle replacement was more cost effective. 28 This observation warrants caution as consideration should also be given to the costs incurred in treating ankle replacement failures, using revision prostheses as well as revisions complicated by infection necessitating amputation. The data are limited and subject to interpretation.…”
Section: Operative Managementmentioning
confidence: 99%